Efeito da moagem do amido de milho na gelatinização e na estabilização cooperativa de emulsões Pickering com quitina - Barros, Matheus de Oliveira (2025)
Pickering emulsions, unlike conventional ones stabilized by surfactants, use colloidal particles as stabilizers, eliminating the need for these agents that can be harmful to health and the environment. Nano-starch, obtained through milling, represents a sustainable approach compared to traditional acid hydrolysis and can also alter interesting properties of starch, such as its gelatinization temperature. To improve the stability of these particles in emulsions, functionalization of starch chains by oxidation with 2-octen-1-ylsuccinic anhydride (OSA) is usually employed; however, sustainable alternatives such as micronization, plasma, and combination with other natural polymers present advantages. Chitin, found in fungi and arthropod exoskeletons, stands out as a stabilizer for Pickering emulsions due to its biocompatible and anti-inflammatory properties, which are highly attractive for food applications. This project aims to explore the effectiveness of ball milling in producing smaller starch particles and verify the modification in their properties. Subsequently, using these colloidal particles obtained in a ball mill along with chitin nanocrystals as a polymer combination technique for stabilizing Pickering emulsions. Ball milling of starch has proven effective in size reduction and was able to decrease the starch gelatinization temperature, with milling times exceeding 10 hours using a starch-to-balls mass ratio of 1:20. The combination of starch milled for 20 hours with chitin nanocrystals proved efficient in stabilizing Pickering emulsions when used in equal concentrations, producing an emulsion with a low droplet size (2.29 µm) and creaming stability superior to one month of storage at room temperature.